Munchausen's syndrome simulating reflex sympathetic dystrophy. Issue 12 (December 1990) - Rodriguez-Moreno, J; Ruiz-Martin, J M; Mateo-Soria, L; Rozadilla, A; Roig-Escofet, D
Abstract : A 15 year old girl who had pain, oedema of her left hand, and fever of four months' duration is described. Marked demineralisation of her hand was shown by radiography, and increased articular uptake by technetium-99m bone scan. All these changes were indistinguishable from reflex sympathetic dystrophy. After two admissions to hospital and multiple explorations we discovered that she had induced her symptoms herself and a diagnosis of Munchausen's syndrome was made. As far as we know this presentation has not been previously reported and might help to explain the physiopathology of some signs of reflex sympathetic dystrophy.